FORMATION OF ECOLOGICAL AESTHETIC EDUCATION IN FUTURE SPECIALISTS - Oygul Ashurova Anvarjonovna (Western European Studies, 2024)
This article explores the development of ecological aesthetic education in future specialists, emphasizing the integration of ecological awareness and aesthetic values into the training process. The research highlights the importance of combining environmental responsibility with aesthetic appreciation, leading to well-rounded professionals who are not only technically proficient but also socially and environmentally conscious. The study reviews current educational approaches, proposes methods for enhancing ecological aesthetic education, and discusses the impact of this integrated approach on the holistic development of future specialists.
Keywords: Ecological aesthetic education; future specialists; environmental awareness